RECOMMENDATION OF BOOKKEEPING MODELS FOR MSMEs: STUDY IN EAST INDONESIAN AREA - Dian Pertiwi; Nur Hidayah (Jurnal Iqtisaduna, 2019)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, including in Eastern Indonesia. However, behind the magnitude of the contribution provided there are still obstacles in its development. Provision and presentation of financial statements is still a problem for MSME players. This study will identify the accounting reporting model conducted by MSMEs, identify the information needs of the capital providers, and offer bookkeeping model for MSMEs. The research method uses a qualitative approach. Data is collected by interview techniques and non-behavioural observations of note analysis. The results of the study indicate that accounting reporting carried out by MSMEs mostly only records cash in and cash out. Information needed by capital providers is information related to business operations, including debt and receivables. Based on the interests of MSMEs and capital providers, a simple bookkeeping model is offered which accommodates accounting principles in the SAK EMKM.